Diverse Effect of Vitamin C and N-Acetylcysteine on Aluminum-Induced Eryptosis - Ali Reza Zangeneh; Mohammad Ali Takhshid; Reza Ranjbaran; Mahsa Maleknia; Mohammad Hassan Meshkibaf (Biochemistry Research International, 2021)
Purpose. The role of oxidative stress in Aluminum (Al)-induced apoptotic effects has been investigated and suicidal death of erythrocytes, eryptosis, is characterized by cell shrinkage and phosphatidylserine externalization (PSE) at the surface of the erythrocyte cell membrane. Eryptosis is stimulated by an increase in cytosolic Ca2+ concentration and reactive oxygen species (ROS). This ex vivo study was conducted to evaluate the effect of well-known antioxidants including vitamin C (vit C) and N-acetylcysteine (NAC), against Al-induced hemolysis and eryptosis. Methods. Isolated erythrocytes from the healthy volunteers were partitioned into various groups (6 replicates/group) and treated by various concentrations of Al (3–100 µM) in the presence and absence of vit C (0.6 mM) and NAC (1 mM). After 24 hours of treatment, hemolysis was determined from hemoglobin levels in the supernatant. Flowcytometric methods were applied to measure PSE, cell shrinkage, Ca2+ content, and ROS abundance using annexin V-binding, forward scatter, Fluo3-fluorescence, and DCFDA dependent fluorescence, respectively. Reduced glutathione (GSH) was measured by the ELISA method. Results. The results showed that a 24 hours’ exposure of the erythrocytes to Al (10–100 µM) significantly increased hemolysis in a dose and Ca2+dependent manner. Al also dramatically decreased forward scatter. The percentage of PSE cells, Fluo3-fluorescence, and DCFDA fluorescence were increased by Al. Furthermore, cotreatment with NAC inhibited the effect of Al on hemolysis, eryptosis, and ROS production. Vit C decreased Al-induced ROS production. However, increased Al-induced eryptosis. There were no significant changes in glutathione after the ALCL3 treatment. Conclusions. Al-induced eryptosis and hemolysis through triggering oxidative stress, while NAC could diverse this effect. In contrast, vit C might intensify Al-induced eryptosis at particular doses through a less known mechanism.